Nitrogen‐doped reduced graphene oxide incorporated porous rod‐like cobalt molybdate as an anode for high‐capacity long‐life lithium‐ion batteries. (15th July 2021) - Shanthappa, R.; Narsimulu, D.; Kakarla, Ashok Kumar; Yu, Jae Su
Summary: Modification of volume expansion and poor conductivity of ternary metal molybdates as an anode for lithium‐ion batteries (LIBs) results in the improvement of their reversibility and rate capability. Herein, porous rod‐like cobalt molybdate incorporated with nitrogen (N) doped reduced graphene oxide (rGO) was fabricated using a silicone oil‐bath method and further heated at 500°C (designated as CMO500@N‐G) and 600°C (CMO600@N‐G). The well‐designed CMO500@N‐G and CMO600@N‐G electrodes were explored as an anode for LIBs. Notably, the CMO500@N‐G electrode exhibited a discharge capacity of 612 mA h g −1 over 250 cycles at 100 mA g −1, while the CMO600@N‐G was restricted to 199.5 mA h g −1 . Besides, the CMO500@N‐G electrode was sustained for 2000 cycles with a remarkable discharge capacity of 665 mA h g −1 even at a high current density of 1000 mA g −1 . Finally, using a newly developed CMO500@N‐G anode, a full cell LIB was also fabricated and showed good reversibility and excellent rate performance. This outstanding performance of the electrode can be ascribed to the unique rod‐like morphology of cobalt molybdate with a highly conductive N doped rGO, which suggests a new strategy to fabricate high‐capacity anode materials for LIBs. Abstract : Porous rod‐like N doped rGO incorporated cobalt molybdates were prepared via a silicone oil‐bath method. The CMO500@N‐G//LNMC@CC coin‐type full cell LIB exhibits good reversibility and excellent rate performance, which is successful powering blue and green light‐emitting diodes.